Pemenuhan Kebijakan Sektor UMKM dan Pedagang Kaki Lima sebagai Pekerja Sektor Informal dalam Peningkatan Kegiatan Perekonomian Pasca Pandemi Covid-19 - Puspitasari, Fransisca Stella Tri; Mukti, Nicolas Rafael Kreshna (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2022)
The deadly Covid-19 pandemic has spread to all corners of the world, causing the downgrade of the health sector, and economic sector, including Indonesia. Government appeals such as physical distancing, social distancing, and stay at home make people's needs decrease and cause economic turbulence, especially for MSMEs and street vendors; they are pillars of income for Indonesia. Considering that MSMEs that survive and experience an increase during the pandemic are those who can connect to the digital ecosystem, MSMEs and street vendors, together with the government, are obliged to carry out sustainable economic transformations such as innovation with the introduction of digitalization to facilitate transactions even though sellers and buyers do not meet up. Therefore as the rule of law, the government has provided convenience related to electronic business licensing for MSMEs and Street Vendors. The steps are followed with regulatory objectives Act Number 6 of 2018 about Health Quarantine although Government decree Number 21 of 2020 about Large-Scale Social Restrictions in the context of Accelerating the Handling of Coronavirus Disease 2019 (Covid-19) must prioritize health protocols even though it has entered the era of Adaptation of New Habits after soaring cases of covid-19. The government also presents MSME PEN Program as MSME Economic Recovery; nevertheless, policy effectiveness for affected MSMEs is more needed during this New Normal Period. Adoption of MSME Effective Restorative Policy is needed now because of the Ultra Micro Assistance movement, Love Local Products, and the Synergy of one MSME Data which is expected to be able to assist the government in implementing policy efficiency following with the realization of the value of Pancasila social justice for the whole of the people of Indonesia in the MSME Effective Restorative Policy.